Analisis Pengukuran Waktu Kerja Dan Beban Kerja Mental Guna Menentukan Jumlah Tenaga Kerja Yang Optimal Pada PT. Papan Jaya Lumajang - Kristian Mangku Setyo Panjaitan; Harsono Teguh S; Achmad Daengs GS; Sugiharto Sugiharto; Bambang Karnain; Rina Dewi (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
PT. Papan Jaya is one of the textile industries that produces ply wood in large quantities. A significant increase in the number of requests forces companies to be able to compete with other companies, so an increase in productivity is needed. The company experienced several periods of non-fulfilment of production targets. Given the problems that occur, this research will calculate the analysis of working time and mental workload on the workforce in order to optimize the workforce. This type of research uses the Work Sampling method to calculate normal time and standard time, NASA-TLX is useful for knowing the value of the mental workload of the workforce, and Work-load Analysis to optimize the workforce. The results of the Work Sampling method obtained a total production time of 70.41 minutes by considering the Performance Rating and Allowance value. The NASA-TLX method results in the majority of the workforce having a high workload value. The mental workload value with the highest value was 86 on the hot press machine (Operator 9) while the lowest mental workload value was 55 on the rotary machine (Operator 4). As well as the results of the Workload Analysis method, the mixing machine part and the cutting machine part need to add 2 workers and the trimming part needs to reduce 1 worker. From these results, the workforce at PT. Papan Jaya, which originally consisted of 18 workers, after being calculated, the results obtained were 21 workers.